Optimasi Pengadaan Beras Dalam Negeri pada Perusahaan Umum BULOG Kantor Wilayah Jawa Barat - Faishal Abdul Aziz; Machfud; Taufik Djatna (JURNAL PANGAN, 2026)
Background: Stability in rice supply and prices is a pillar of national food security, and the Public Company (Perum) BULOG plays a central role. However, Perum BULOG faces dual challenges: fulfilling government assignments (Public Service Obligations) and achieving positive financial performance. Objectives: This study aims to analyze the optimal level of domestic rice procurement at the Perum BULOG West Java Regional Office to maximize Earnings Before Interest, Taxes, Depreciation, and Amortization (EBITDA) while still considering five priority objectives under two scenarios. Methods: The optimization method used is Pre-emptive Goal Programming, a multi- objective, multi-level approach that minimizes deviations from the five objectives in priority order. The data analyzed are secondary data from 2024 from four Branch Offices (Kancab) in West Java: Kancab Bandung, Cirebon, Indramayu, and Bogor. Results and Discussion: The results show that the main factors influencing rice procurement are price, harvest area, production, warehouse capacity, and market certainty from government programs. In the First Scenario, Priority 1's objective, minimizing overprocurement (d ⁺ ₁), was fully achieved with a deviation of 0.00. This means that all annual procurement targets were met, resulting in the optimal domestic rice procurement of 86,500,000 kg, in line with the target. EBITDA in the First Scenario was IDR 323.21 billion, a 78.34% decrease from the actual figure of IDR1,492.22 billion. In the Second Scenario, Priority 1's objective, minimizing undersales (d ⁻ ₅), was fully achieved with a deviation of 0.00. This means that all sales targets were optimally met. EBITDA in the Second Scenario was IDR461.21 billion, a 69.09 percent decrease from the actual figure of IDR1,492.22 billion. Conclusion: The optimization model indicates that the priority structure determines the achievement of rice procurement targets; therefore, a more balanced procurement policy is needed through resource optimization, logistics integration, and the strengthening of adaptive strategies to support supply stability and financial performance.